2019
DOI: 10.1136/thoraxjnl-2018-212203
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the association between bronchiolitis in infancy and recurrent wheeze: a whole English birth cohort case–control study

Abstract: The precise association between bronchiolitis and predisposition to childhood wheeze is unclear. We assessed bronchiolitis aetiology and later wheeze phenotypes in the entire 2007 English birth cohort. All infants admitted to hospital in England during their first year of life with bronchiolitis or urinary tract infection (UTI) were followed using Hospital Episode Statistics to determine risk and characteristics of wheeze admission over the subsequent 8 years. In our cohort of 21 272 children compared with UTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Marlow et al 6 confirmed the association between infants with bronchiolitis and wheeze, but his study lacks some information that is missed when using discharge codes. The authors reported that a group of infants had bronchiolitis caused by RSV, but they did not describe the aetiological agents in the other two groups.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…Marlow et al 6 confirmed the association between infants with bronchiolitis and wheeze, but his study lacks some information that is missed when using discharge codes. The authors reported that a group of infants had bronchiolitis caused by RSV, but they did not describe the aetiological agents in the other two groups.…”
mentioning
confidence: 95%
“…Marlow et al 6 confirmed the association between bronchiolitis and wheeze, but the question is still open. Is it RSV that causes bronchial hypersensitivity and the development of asthma or rather, does the virus identify those infants that have a genetic predisposition for the development of RW and asthma?…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…3 Previous birth cohort and post-bronchiolitis studies reported that bronchiolitis and wheezing in early childhood may have long-term effects on respiratory health. 4,5 Wheezing and asthma symptoms, although common after bronchiolitis at preschool age, usually improve at school age. However, after puberty, the symptoms may recur, even in those without any symptom recurrence after bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%